Hyperphosphataemia: Treatment Options - Malberti, Fabio (Drugs (New York, N.Y.), 2013)
Hyperphosphataemia can be induced by three main conditions: a massive acute phosphate load, a primary increase in renal phosphate reabsorption, and an impaired renal phosphate excretion due to acute or chronic renal insufficiency. Renal excretion is so efficient in normal subjects that balance can be maintained with only a minimal rise in serum phosphorus concentration even for a large phosphorus load. Therefore, acute hyperphosphataemia usually resolves within few hours if renal function is intact. The most frequent cause of chronic hyperphosphataemia is chronic renal failure. Hyperphosphataemia in chronic kidney disease (CKD) is associated with increased cardiovascular morbidity and mortality. Lowering the phosphate load and maintaining serum phosphorus levels within the normal range are considered important therapeutic goals to improve clinical outcomes in CKD patients. Treatment consists of diminishing intestinal phosphate absorption by a low phosphate diet and phosphate binders. In CKD patients on dialysis an efficient dialysis removal of phosphate should be ensured. Dietary restriction of phosphorus while maintaining adequate protein intake is not sufficient to control serum phosphate levels in most CKD patients; therefore, the prescription of a phosphate binder is required. Aluminium-containing agents are efficient but no longer widely used because of their toxicity. Calcium-based salts are inexpensive, effective and most widely used, but there is now concern about their association with hypercalcaemia, parathyroid gland suppression, adynamic bone disease, and vascular and extraosseous calcification. The average daily dose of calcium acetate or carbonate prescribed in the randomised controlled trials to control hyperphosphataemia in dialysis patients ranges between 1.2 and 2.3 g of elemental calcium. Such doses are greater than the recommended dietary calcium intake and can lead to a positive calcium balance. Although large amounts of calcium salts should probably be avoided, modest doses (<1 g of elemental calcium) may represent a reasonable initial approach to reduced serum phosphorus levels. A non-calcium-based binder can then be added when large doses of binder are required. At present, there are three types of non-calcium-based phosphate binders available: sevelamer, lanthanum carbonate and magnesium salts. Each of these compounds is as effective as calcium salts in lowering serum phosphorus levels depending on an adequate prescribed dose and adherence of the patient to treatment. Sevelamer is the only non-calcium-containing phosphate binder that does not have potential for systemic accumulation and presents pleiotropic effects that may impact on cardiovascular disease. In contrast, lanthanum carbonate and magnesium salts are absorbed in the gut and their route of excretion is biliary for lanthanum and urinary for magnesium. There are insufficient data to establish the comparative superiority of non-calcium binding agents over calcium salts for such important patient-level outcomes as all-cause mortality and cardiovascular end points. Moreover, full adoption of sevelamer and lanthanum by government drug reimbursement agencies in place of calcium salts would lead to a large increase in health-care expenditure. Therefore, the choice of phosphate binder should be individualised, considering the clinical context, the costs, and the individual tolerability the concomitant effects on other parameters of mineral metabolism, such as serum calcium and parathyroid hormone, besides those on serum phosphorus.